1997
DOI: 10.1161/01.atv.17.10.2177
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Calcium and G Proteins in the Acute Release of Tissue-Type Plasminogen Activator and von Willebrand Factor From Cultured Human Endothelial Cells

Abstract: In this study, we investigated the role of Ca2+ and G proteins in thrombin-induced acute release (regulated secretion) of tissue-type plasminogen activator (TPA) and von Willebrand factor (vWF), using a previously described system of primary human umbilical vein endothelial cells (HUVECs). The acute release of TPA and vWF, as induced by alpha-thrombin, was almost zero after chelation of Ca2+i, showing that an increase in [Ca2+]i was required. It did not matter whether the increase in [Ca2+]i came from an intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 53 publications
3
45
1
1
Order By: Relevance
“…Differential pathways of VWF and t-PA release in HUVECs with respect to pertussis toxin sensitivity and levels of intracellular Ca 2ϩ have been described. 37 These functional differences may have a structural explanation, because it has been observed that t-PA is stored in small dense vesicles distinct from WPBs. 38 However, this observation is controversial because other studies have shown that t-PA is stored in WPBs in HUVECs.…”
Section: Selective Release Of Weibel-palade Bodies That Contain Predomentioning
confidence: 99%
“…Differential pathways of VWF and t-PA release in HUVECs with respect to pertussis toxin sensitivity and levels of intracellular Ca 2ϩ have been described. 37 These functional differences may have a structural explanation, because it has been observed that t-PA is stored in small dense vesicles distinct from WPBs. 38 However, this observation is controversial because other studies have shown that t-PA is stored in WPBs in HUVECs.…”
Section: Selective Release Of Weibel-palade Bodies That Contain Predomentioning
confidence: 99%
“…low pH) to avoid preanalytical complex binding with PAI-1 [44]. Regulated release of t-PA from endothelial cells can be induced by a number of substances with the common denominator that they activate G-protein-coupled cell surface receptors [45]. Several products formed during thrombus formation, i.e.…”
Section: Regulation Of Intravascular Fibrinolysis In Vivomentioning
confidence: 99%
“…15,16 Inhibition studies have shown that intracellular Ca 2ϩ exerts its effect on regulated secretion of vWF via calmodulin. 13,15 …”
mentioning
confidence: 99%
“…10 -12 The mechanism of thrombin-induced exocytosis of Weibel-Palade bodies has been only partially elucidated. [13][14][15] Thrombin induces the elevation of intracellular Ca 2ϩ levels, which appears crucial for the release of vWF from WeibelPalade bodies. 15,16 Inhibition studies have shown that intracellular Ca 2ϩ exerts its effect on regulated secretion of vWF via calmodulin.…”
mentioning
confidence: 99%